2016
DOI: 10.1111/polp.12154
|View full text |Cite
|
Sign up to set email alerts
|

Coalition Politics and Inter‐Party Conflict Management: A Theoretical Framework

Abstract: Inter-party conflict management is a typical coalitional problem in parliamentary governments. To study how and why conflicts in coalitions emerge and how parties cope with them can enhance our knowledge of coalition governance. Here, I propose a framework for comparative studies on the topic. The framework is based on the conception of coalition politics as politics of exchange. It looks at interparty interactions, but also accounts for the impact of intra-party politics. Moreover, I provide a classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 90 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…For the purposes of our research, therefore, we explore instigator-defender policy scenarios using perspectives from the literature on policy conflict. Policy conflict captures many types of situations in which actors take contrasting positions related to public policy (Vercesi, 2016) and where one actor's policy positions can threaten other actors (Weible & Heikkila, 2017). The literature often treats all policy conflict situations as if the level of conflict is static in time (Heidbreder et al, 2011;Matland, 1995).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…For the purposes of our research, therefore, we explore instigator-defender policy scenarios using perspectives from the literature on policy conflict. Policy conflict captures many types of situations in which actors take contrasting positions related to public policy (Vercesi, 2016) and where one actor's policy positions can threaten other actors (Weible & Heikkila, 2017). The literature often treats all policy conflict situations as if the level of conflict is static in time (Heidbreder et al, 2011;Matland, 1995).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…As a third step, I investigate those coalition mechanisms that involve the whole coalition, including party members outside the executive (Vercesi 2016). In our case, the coalition agreement ('Contract for the Government of Change') is a postelectoral pact drafted (among others) by party leaders who became ministers.…”
Section: Extra-parliamentary Arenamentioning
confidence: 99%
“…These distances can have a psychological meaning for political actors (Grofman, 1982;Laver, 1998). In this sense, it has been shown that the increase of this distance makes coalition formation more difficult (Hinckley, 1972;Bäck & Dumont, 2008, Vercesi, 2016. Besides, parties that are ideologically close are more likely to share overlapping voters (Martin & Vanberg, 2003), and they are driven to assess possible coalitions drawing on their expectations about the closeness of the future government with their own political positions (Bäck, 2003).…”
Section: Tablementioning
confidence: 99%